Windows XP - Fehily, Chris (Visual quickstart guide., 2003)
If you have Windows XP on your computer, you'll want Windows XP: Visual QuickStart Guide on your bookshelf-it's as simple as that. Even veteran Windows users will quickly discover that the changes in Windows XP go far beyond a radically redesigned interface. And to get the most out of this powerful new operating system-including all of its bundled software and goodies-there's no place better to start than the straightforward, task-oriented approach of Peachpit's popular Visual QuickStart series. In this volume, veteran author Chris Fehily gets right down to business, covering both Home and Professional versions of Microsoft's redesigned operating system in this single edition. After a thorough introduction to the new interface, chapters cover topics such as installing and removing programs; working with documents, accessories, and multimedia; going online; printing; hardware issues; maintenance; and more. Along the way you'll find plenty of screen shots and other graphic aids to acclimate you to all that's new in Microsoft's operating system, as well as the types of undocumented tips and tricks that can only be gleaned from hard-won experience-the author's, not yours!.